IMPLEMENTATION OF STANDARD OPERATING PROCEDURES AT ROOM SERVICE ANGKASA GARDEN HOTEL PEKANBARU - Menda Aulia Sari; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The key to the success of a hotel is the implementation of Standard Operating Procedures (SOP) in accordance with the standards set by each hotel, so that visitors feel satisfied, comfortable and want to return to visit a hotel. Room service at Angkasa Garden Hotel Pekanbaru has a predetermined Standard Operating Procedure (SOP), but there are several obstacles in implementing the Standard Operating Procedure (SOP). This study aims to determine the implementation of Standard Operating Procedures (SOP) in Room service Angkasa Garden Hotel Pekanbaru. This study uses a qualitative method with a descriptive approach. Data collection techniques used in the study were interviews, observation, and documentation. Informants involved in this study were Mr. Doni as manager of food & beverage service department of Angkasa Garden Hotel Pekanbaru, Mr. Indra as waiter of food & beverage service department of Angkasa Garden Hotel Pekanbaru and Mrs. Ria as waiters of food & beverage service department of Angkasa Garden Hotel Pekanbaru. Based on the results of the research, the implementation of Standard Operating Procedures (SOP) in Room service Angkasa Garden Hotel Pekanbaru has been implemented properly in accordance with the operational standards that have been set by the hotel. As for the implementation of Standard Operating Procedures (SOP) at the room service of Angkasa Garden Hotel, Pekanbaru, namely receiving orders from the telephone, making captain orders, preparing equipment, orders delivered to guest rooms and clear-up. Constraints faced in the implementation of Standard Operating Procedures (SOP) are related to the small number of employees and there are still many in the menu list that are not available. Keywords : Standard Operating Procedures, Room Service, Hotel.